Synthesis and Characterization of Praseodymium Doped Nickel Zinc Ferrites using Microemulsion Method - Khan Asghar, H. M. Noor ul Huda; Nawaz, Muhammad Kamran; Hussain, Rafaqat; Gilani , Zaheer Abbas (Journal of Materials and Physical Sciences, 2020)
Spinel ferrites nanoparticles are plays important role in our daily life. Praseodymium doped Nickel Zinc Ferrite Nanoparticles having general formula Ni0.3Zn0.7PrxFe2-xO4 (x=0.00, 0.025, 0.050, 0.075 and 0.1) were synthesized by microemulsion method. X-Ray diffraction (XRD) was used to find different parameters of crystalline size. The development of the FCC spinel structure was observed by XRD data. The most intense peak of the XRD was identified at 2?=35º.From Debye sherrer's formula, calculated the crystalline size 15nm to 29nm ranges. The lattice constant calculations are decreased with the doping of Praseodymium (Pr3+) contents. The x-ray density increases as the concentration of Praseodymium (Pr3+) doping increases, Because Praseodymium (Pr3+) ion has a greater molar weight than Fe3+ ion. The Absorption band spectra are analyzed by using Fourier Transform Infrared spectroscopy (FTIR).The absorption bands ?1 is known as octahedral stretching bands were found to be in the range of 414 cm-1 and ?2 is the tetrahedral stretching band were found to be in the range of 530cm-1.Dielectric properties of Praseodymium doped Nickel-Zinc Ferrite were measured with impedance Analyzer in the frequency of 1 MHz to 3 GHz range. When Pr3+content concentration increases, the dielectric characteristics, such as dielectric constant, dielectric loss, and tangent loss were also decreased. These measured dielectric characteristics showed that these nanomaterials may be used in higher frequencies devices.